2021
DOI: 10.15212/bioi-2020-0047
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Toxicity and Challenges in Transferability of Surface-functionalized Metallic Nanoparticles from Animal Models to Humans

Abstract: The unique size and surface morphology of nanoparticles (NPs) have substantially influenced all aspects of human life, making nanotechnology a novel and promising field for various applications in biomedical sciences. Metallic NPs have gained immense interest over the last few decades due to their promising optical, electrical, and biological properties. However, the aggregation and the toxic nature of these NPs have restricted their utilization in more optimized applications. The optimum selection of biopolym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…The facile green approach of chitosanloaded bioengineered AgNPs using ethanolic extract of Syzygium aromaticum shows excellent biocompatibility and cytotoxicity against HeLa cells and thus can be utilized as a potential theragnostic agent in the medical field. 82 The phytofabrication of green synthesized magnesium oxide NPs (G-MgO NPs) using Calotropis gigantea flower extract shows higher biocompatibility in embryonic zebrafish by attenuating molecular nanotoxicity via the apoptotic pathway as compared to magnesium oxide NPs (MgONPs). 83 Furthermore, the harmful effect increases with decreasing NP size.…”
Section: Exploring Biocompatibility and Toxicity Studies Of Green Syn...mentioning
confidence: 99%
“…The facile green approach of chitosanloaded bioengineered AgNPs using ethanolic extract of Syzygium aromaticum shows excellent biocompatibility and cytotoxicity against HeLa cells and thus can be utilized as a potential theragnostic agent in the medical field. 82 The phytofabrication of green synthesized magnesium oxide NPs (G-MgO NPs) using Calotropis gigantea flower extract shows higher biocompatibility in embryonic zebrafish by attenuating molecular nanotoxicity via the apoptotic pathway as compared to magnesium oxide NPs (MgONPs). 83 Furthermore, the harmful effect increases with decreasing NP size.…”
Section: Exploring Biocompatibility and Toxicity Studies Of Green Syn...mentioning
confidence: 99%
“…The pore size and surface ratio of matrices have also been proven to impact protein capture onto adsorbents (Todokoro et al, 2002;Sakata et al, 2017). Although nanoparticles (especially metallic nanoparticles) have gained immense interest as the matrices of adsorbents resulting from their excellent electrical properties, the toxicity and adverse effects of the use of metallic nanoparticles have been reported (Asghar et al, 2021). Nanoparticles are usually designed to be injected into the bloodstream directly, making it extremely important to assess the behaviors of nanoparticles with different ligands in biological fluids (Abd Ellah and Abouelmagd, 2017).…”
Section: Biocompatibilitymentioning
confidence: 99%
“…Nanocomposites of inorganic metals with different polymers are gaining attraction and scientific importance. It has been reported that the metallic NPs incorporation in polymer matrix significantly improved the performance of nanocomposite at a lower cost [6]. Metallic NPs have been synthesized after conjugation with various polymers like graphene oxide, chitosan, carboxymethyl cellulose (CMC), gelatin, lactic acid, guar gum and polyethersulphoneand many others [7][8][9].…”
Section: Introductionmentioning
confidence: 99%